Structure–property relationship study of Nafion XL membrane for high-rate, long-lifespan, and all-climate vanadium flow batteries. Issue 50 (19th June 2017) - Yu, Lihong; Lin, Feng; Xu, Ling; Xi, Jingyu
Abstract : The sandwich-structured Nafion XL membrane is promising for vanadium flow batteries to achieve high-rate performance, super-long lifespan and broad temperature adaptability. Abstract : Vanadium flow batteries (VFB) have become one of the most promising large-scale energy storage technologies owing to their overwhelming advantage in lifespan and power. Development of highly efficient, durable and low-cost ion exchange membranes is essential to the practical application of VFB. In this work, we report an ultra-thin sandwich structure membrane (Nafion XL), as a promising alternative to the widely used Nafion 212 and 115 membranes. By combination of the mechanical reinforcement though the microporous PTFE middle layer (∼10 μm) and fast proton transport through the two dense Nafion outer layers (∼10 μm), the Nafion XL membrane shows lower area resistance and slower vanadium ion crossover than the Nafion 212 and 115 membranes. As a result, the Nafion XL membrane-based VFB single cell demonstrates excellent rate capability (40–400 mA cm −2 ), superior long-term cycling stability (2200 cycles@120/200 mA cm −2 ) and wide temperature adaptability (−20 to 50 °C). The results reported herein are beneficial for the development of high-rate, long-lifespan, and all-climate VFB for sustainable energy storage.